A cDNA clone encoding a photosystem I protein with homology to photosystem II chlorophyll a/b-binding polypeptides. - Hoffman, N E (1987)
We report here the isolation and nucleotide sequence of a complete cDNA clone encoding a photosystem I (PS I) polypeptide that is recognized by a monoclonal antibody made against photosystem II (PS II) chlorophyll a/b-binding (CAB) proteins. The deduced sequence of this PS I protein shows 30% overall identity to PS II CAB sequences, and two long segments within this protein show 50% and 65% identity to the corresponding segments in the PS II CAB polypeptides. Even though the sequence of this PS I CAB protein is substantially divergent from PS II CAB sequences, their hydropathy plots are very similar and suggest they all traverse the thylakoid membrane three times. A segment of the PS I CAB polypeptide shows similarity to the functionally analogous beta subunits of the antenna proteins of purple bacteria. In contrast, no homology was observed between these bacterial proteins and PS II CAB polypeptides.